Interstellar scintillation and annual cycles in the BL Lac source PKS 1519-273 - Jauncey, D.; Johnston, H.; Bignall, Hayley; Lovell, J.; Kedziora-Chudczer, L.; Tzioumis, A.; Macquart, Jean-Pierre (Kluwer Academic Publishers., 2003)
We have measured annual cycles in the time scales of the rapid, intra-day variability of the total and circularly polarized flux density, of the unusual BL Lac source PKS 1519-273 at 4.8 and 8.6 GHz. The data were collected at the ATCA over the last seven years, and establish unequivocally interstellar scintillation as the principal mechanism responsible for this cm-wavelength intra-day variability.